PENERAPAN PBL MELALUI PEMBUATAN TAMAN RUMPUT PADA MATERI LINGKARAN DI KELAS VIII - Dian Septa Novari; Indah Widyaningrum; Widiawati W. (JOURNAL of MATHEMATICS SCIENCE and EDUCATION, 2019)
This study aims to determine 1) the student's activity during the implementation of PBL models and 2) student learning outcomes after the implementation of PBL models through the creation of grass park on the material circle in class VIII SMP Negeri 1 Pagaralam. This research is an experimental research category one shot case study involving 32 students of class VIII SMP Negeri 1 Pagaralam. The results showed that the activity of students during the loading applied to the model PBL through grass park is categorized as very active seen from the activity of visual, verbal, listening, metrics, and writing. While student learning outcomes after the implementation of the PBL model through the creation of grass park are categorized very well as indicated by the average value of students. Thus, the PBL model is very suitable for use in mathematics, especially in the area of a circle of matter.